Wavefront Sensor for the Determination of Nanostructured Surface Defects - V.V. Buchenko; A.A. Goloborodko; V.V. Lendel; O.S. Oberemok (Журнал нано- та електронної фізики)
The comparison of the theoretical calculations and experimental results of the influence of interference phenomena on the determination of the parameters and the structure of the refractive index is presented. The feature of the original wave formation in the system of double Fourier transform with the reflection of light from the surface with structured local inhomogeneities of the refractive index is shown. The theoretical analysis and computer simulation of the wavefront sensor operation to detect the spatial distribution of the refractive index are performed. It is proposed to use the wavefront phase dispersion to determine the direction of the refractive index change.